TAM KJ‐Q14 ESU and TAM 12J‐39 ESU upland cotton germplasm with improved fiber bundle strength. Issue 2 (6th May 2021) - Smith, C. Wayne; Joy, Kolbyn; Hague, Steve; Hequet, Eric; Kelly, Brendan; Jones, Don
Abstract: Production of quality cotton yarns depends on cotton fibers that are long, strong, and uniform in length. Upland cotton ( Gossypium hirsutum L.) yarn produced in the United States is spun predominately on open‐end spinning technology, while globally, ring technology predominates. Open‐end technology offers speed of production, while ring offers flexibility in size and quality of yarn. A newer technology, vortex spinning, provides spinning speeds that exceed that of open‐end spinning and is 30 times that of ring spinning. In order for upland cotton fibers to compete with man‐made fibers as newer technology is adopted, breeders must develop genotypes that produce longer, stronger, and finer fibers that are more uniform in length distribution. The Cotton Improvement Program at Texas A&M AgriLife Research has developed and released upland cotton germplasm with fiber length equal to that of pima cotton ( G. barbadense L.) and fiber strength greater than upland cultivars currently marketed. TAM KJ‐Q14 ESU (extra strength upland) and TAM 12J‐39 ESU (Reg. no. GP‐1084, PI 698109 and Reg. no. GP‐1085 PI 698110, respectively) were developed as part of the effort to provide upland cotton breeders with parental material to incorporate fiber strength into new cultivars. TAM KJ‐Q14 ESU combines excellent fiber length with fiber strength exceeding 350 kN m kg –1 while TAM 12J‐39 ESU combines competitive yield potential with fiber strength exceeding 350 kN m kg –1 . Both germplasm lines will provide breeders with additional sources of excellent fiber strength in good to excellent agronomic profiles. Core Ideas: Fiber strength of cotton fibers sufficient to withstand the stress of high‐speed processing. Fiber bundle strength of cotton fibers required for newer spinning technology. TAM 12J‐39 ESU combines exceptional fiber bundle strength with broad agronomic adaptability. TAM JK‐Q14 ESU combines improved fiber bundle strength and fiber length.